ANALYSIS OF INA-CBG'S FARE AND GOVERNOR REGULATION FAREON SURGERY AT INPATIENT ROOM OF UNDATA REGIONAL PUBLIC HOSPITAL IN PALU - Napirah, Muhammad Ryman; Nurul, Rasyika; Anggraeni, Riru Dwi (Public Health of Indonesia, 2016)
Aim: In order to determine the fares of surgery, there are two types of fares used by hospitals namely Indonesian Case Based Groups fare (INA-CBG s) and Governor Regulation fare. This study aimed to identify and analyze both types of fares in orthopedic surgery, general, eyes, midwifery, mouth, ENT, urology at inpatient room of Undata Regional Public Hospital in Palu during year 2014.Method: This was a quantitative study with descriptive approach with 46 cases as the number of surgery. Data were collected through observation and analysis of secondary data were gotten from medical record, pharmaceutical installation of IBS/IDR, inpatient therapy room (Matahari, Aster, and Teratai pavilions) and cashier of inpatient room in form of cost details and patient data from January to December 2014. Data Presentation was formed on tables, where the existing fares are grouped based on the component of each cost then summed and calculated the deviation between the two types of fares.Results: This study indicated that orthopedic surgery with deviation of Rp 11.311.365, general surgery with deviation of Rp 6.438.409, eyes surgery with deviation of Rp 45.173.741, midwifery surgery with deviation of Rp 6.645.765, oral surgery with deviation of Rp 6.105.659, and urological surgery with deviation of Rp. 3.809.959.Conclusion: It can be concluded that INA-CBG's fares are higher than Governor Regulation fares except orthopedic surgery, where the Governor Regulation faresare higher than INA-CBG's fares. Key Words :INA-CBG's Fares, Governor Regulation Fares,Surgery